Introducing Climate-Smart Mapping and Adaptation Planning in Cambodia - Bernardo, Eisen (International Rice Research Institute, 2022)
To provide technical support on participatory climate-risk mapping and adaptation planning, the CGIAR Initiative on Asian Mega-Deltas conducted a training workshop on Climate-Smart Mapping and Adaptation Planning (CS-MAP) for local research partners in Phnom Penh, Cambodia on 19-20 December 2022. The workshop introduced the CS-MAP approach as the tool for conducting the mapping activities in the AMD target provinces in Cambodia, such as Kandal, Takeo, Prey Vieng, and Svay Rieng.